E-061 Safety and efficacy of Neuroform 3 for intracranial aneurysms treatment. (16th November 2010) - Bonafe, A; Biondi, A
Abstract : Objectives: To assess the feasibility and the clinical performance of NF3 in intracranial aneurysms treatment. SENAT (Safety and Efficacy of Neuroform 3 for Intracranial Aneurysms Treatment) a multicenter registry, has been conducted between January through July 2009 from French centers. The registry protocol allowed for use of all types of coils and adjunctive technologies, as deemed appropriate by the participating investigator. Acute clinical and angiographic assessments were self- reported. Methods: 118 patients (79 women, 39 men) harboring a single aneurysm (109 unruptured, nine ruptured) were treated by means of stent assisted coiling and included in a prospectively maintained database. Aneurysms were predominantly located in the anterior circulation (106 of 118) with a mean size of 6.60 mm (3.55 mm). All patients underwent a double antiplatelet regimen (clopidogrel, aspirin) before, during and after the procedure. Results: Feasibility: Technical success defined as successful stent delivery in the proper place was achieved in 98.2% of cases with one (113 cases) or two (4 cases) devices. In one case of ruptured aneurysm the intended stenting initially considered was abandoned. Safety: 10 (8.5%) per procedural and immediate postprocedural complications occurred: one case of subarachnoid rebleeding due to aneurysmal perforation, one case of delayed bleeding in an infarcted area remote from the stent landing zone, three thrombotic complications and five groin hematomas. Mortality/morbidity: 30 day mortality and morbidity rates were 0% and 4.2% respectively. Adverse events associated with transient or permanent neurological deficit were encountered in 2.6% of cases with the majority occurring in ruptured aneurysms. Acute results: Complete aneurysmal occlusion was achieved in 74 cases (62.7%), residual neck were noted in 28 cases (23.7%) and a residual sac was present in 16 cases (13.6%). Conclusion: The Neuroform Stent 3 has no technical limitation, all types of aneurysm location being amenable to stenting, and does not impair adequate coil embolization. Antiplatelet agents decrease thromboembolic events rate but favor major peripheral or cerebral bleeding preventing larger use of Neuroform stents in cases of acutely rupture aneurysms.